Role of Relative Humidity in Processing and Storage of Seeds and Assessment of Variability in Storage Behaviour in Brassica spp. and Eruca sativa. (30th December 2013) - Suma, A.; Sreenivasan, Kalyani; Singh, A. K.; Radhamani, J.
Abstract : The role of relative humidity (RH) while processing and storing seeds of Brassica spp. and Eruca sativa was investigated by creating different levels of relative humidity, namely, 75%, 50%, 32%, and 11% using different saturated salt solutions and 1% RH using concentrated sulphuric acid. The variability in seed storage behaviour of different species of Brassica was also evaluated. The samples were stored at 40 ± 2 ° C in sealed containers and various physiological parameters were assessed at different intervals up to three months. The seed viability and seedling vigour parameters were considerably reduced in all accessions at high relative humidity irrespective of the species. Storage at intermediate relative humidities caused minimal decline in viability. All the accessions performed better at relative humidity level of 32% maintaining seed moisture content of 3%. On analyzing the variability in storage behaviour, B. rapa and B. juncea were better performers than B. napus and Eruca sativa .